NSM systems - Sena-Cruz, José (2016)
This chapter gives an overview on the state-of-the-art of the Near-Surface Mounted (NSM) technique for structural retrofitting of reinforced concrete structures using Fibre Reinforced Polymers (FRP). The chapter is divided in 5 sections. Firstly, general aspects of the technique are introduced, including main advantages, nomenclature adopted, type of FRP reinforcement and adhesive used, groove geometry/location, and constructional aspects. Then, the existing knowledge on the bond behaviour is addressed focusing on the performed experimental investigations, results, and conclusions in terms of test setups, failure modes, and influence of different parameters on the bond performance. The performance of the existing local bond-slip behaviour laws, both proposed by codes and researches, is also addressed. Similar analysis is also followed for the case of flexural strengthening. The current state on shear strengthening includes two formulations for predicting the NSM shear carrying capacity. The chapter ends with a concluding section summarizing the current state and identifying the needs for future research.